A Responsive and Fair Approach to Trialling Women Perpetrators of Corruption Crimes (Case Study of Corruption Cases with Female Perpetrators in Case Number 28/2022 at the Pontianak District Court) - Syarifudin, Urif; Azis, Hasnah; Rahmaddani, Imam (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper discusses the issue of village fund corruption through a case study involving the defendant, Feridiyana, a 29-year-old woman charged with engaging in a criminal act of corruption during her tenure as the Head of Financial Affairs in Sepang Village, Toho District, Mempawah Regency, West Kalimantan. Feridiyana was charged under Article 3 of the Anti-Corruption Law for her involvement in the misappropriation of village funds, which resulted in a state financial loss of Rp225,229,176.25. Using a gender-responsive and fair approach, this paper examines the subordinate role played by the defendant in the crime, as well as the pressure exerted by the main actor, the Village Head, Joni Fri Harianto. This research emphasises the importance of courts considering the social context differences between male and female perpetrators in corruption cases to prevent gender bias. The findings aim to provide new insights for law enforcement in adjudicating corruption cases involving women and to encourage more inclusive policies within Indonesia's criminal justice system.